AESTHETIC TEXT SPELL TETOMEH VILLAGERS SEI KUBU SUBDISTRICT KUBU ROKAN HILIR REGENCY - Dermawan, Hendra Dermawan Hendra; Jalil, Abdul Jalil Abdul; Rumadi, Hadi Rumadi Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT:This study discusses the aesthetic text spells tetomeh villagers Sei Kubu Kubu subdistrict Rokan Hilir district. As for the problem in this research is how the aesthetics of sound and subtitle language spell tetomeh Sei Kubu villagers Rokan Hilir district consisting of rhythm (metrum and rhythm), efoni, kakafoni, anaphora, Epistrophe, alliteration, assonance, onomatopoeic, vocabulary, and diction. The method used in this research is descriptive quantitative method. The data in this study is the text spells tetomeh villagers Sei Kubu Kubu subdistrict Rokan Hilir district. The form of the data in the form of repetition of phonemes, syllables, words, and phrases. Data collection techniques in this study is the observation in order to find out the availability of data and general information about text spells tetomeh, then do a live interview to the informant, and then record the results of interviews with informants, and last, recorded interviews about what is conveyed by informants . Based on research results, be concluded that, the authors found (1) 45 Data metrum, (1) 76 Data rhythm with classification (20 Data rhythm early, middle rhythm of data 20, 16, crossed the data rhythm, and rhythm 20 reps), (2) 47 Data efoni, (4) 19 Data kakafoni, (4) 10 data anaphora, (5) 20 Data Epistrophe, (6) (7) 42 Data alliteration, (8) 27 Data assonance, (9) 48 Data vocabulary, and (10) 12 Data diction. The results of this study indicate that the aesthetic essence is the ability of an object to attract someone through maupan beauty ugliness. Keywords: Aesthetics, text spells tetomeh